Clinical outcomes following Impella escalation in cardiogenic shock: a single-centre case series highlighting the gap between haemodynamic improvement and survival - Aratame, Atsutaka; Kaku, Daisuke; Baba, Toshio (AME Case Reports; Vol 10 (July 30, 2026): AME Case Reports, 2026)
Background: The use of temporary mechanical circulatory support has increased in patients with cardiogenic shock, particularly those with acute myocardial infarction (AMI). Impella provides effective left ventricular unloading and haemodynamic stabilisation. Escalation of such systems to higher-flow devices (e.g., Impella 5.0/5.5) has been proposed for patients with inadequate responses to Impella CP; however, the clinical impact and optimal timing of this approach remain unclear.Case Description: We conducted a single-centre retrospective case series of patients who underwent Impella escalation between September 2020 and March 2026. Their clinical characteristics, haemodynamic responses, and outcomes were analysed. Among 130 patients treated with Impella CP, eight underwent upgrades. The underlying aetiology was AMI in six patients and myocarditis in two. Six patients required ECPELLA support. Following the upgrades, four patients were successfully weaned off extracorporeal membrane oxygenation (ECMO). Despite haemodynamic improvements, the overall outcomes were poor. Thirty-day survival was achieved in four patients; however, three experienced severe frailty (Clinical Frailty Scale scores of 7–8). Only one patient survived until hospital discharge. Infection-related complications, particularly sepsis, represented the leading causes of death. Device-related complications (e.g., access site infections) were observed in five patients, who required continuous negative-pressure wound therapy.Conclusions: Impella escalation may facilitate haemodynamic stabilisation and ECMO-weaning in selected patients; however, this may not necessarily translate into improved survival outcomes. Non-haemodynamic factors (e.g., infection and frailty) likely play critical roles in determining patient outcomes. These findings should not be interpreted as evidence against Impella escalation itself, but rather highlight the importance of careful patient selection, comprehensive clinical assessment beyond haemodynamic parameters, and further investigation into the optimal timing of escalation.